The Role Islamic Education in Shaping the Religious Character Generation Z in the Era of Digital Technology Development - Ramadhani, Noviana Dwi; Shohib, Muhammad Wildan (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Development digital technology has bring significant changes to the behavioral patterns, value systems, and character of Generation Z. The high intensity of digital media use without value guidance has the potential to weaken religious character, such as a decrease in religious awareness, low media ethics, and a tendency towards individualism. This condition demands the role of adaptive and contextual Islamic education in shaping the religious character of Generation Z in the digital era. This study aims to analyze educational strategies Islam, as well as methods and educational approach Islam in shaping the religious character of generation Z amidst the development of digital technology. This research uses a qualitative approach with a literature study method. Data were collected through documentation and scientific literature searches in the form of national and international journal articles, several of which are available. indexed on Google Scholars, and academic documents that discuss Islamic education, religious character, generation Z, and the development of digital technology, which published in the period 2021–2026, with focus on the theme education Islam, character religious, generation Z, And digital technology . Data analysis was conducted using content analysis with a thematic approach, which included data reduction, data presentation, and conclusion drawing. The results indicate that effective Islamic education strategies for shaping the religious character of Generation Z include integrating Islamic values with digital technology, strengthening holistic religious character education, exemplary educators, and collaboration between schools, families, and the digital environment. Furthermore, religious habituation methods, including dia logue, And reflective, as well as approach humanistic, contextual, And integrative proven relevant in internalizing religious values in generation Z. This study concludes that education Islam own role strategic in form character religious Generation Z in the digital era if designed adaptively, sustainably, and in line with the dynamics of technological developments.